2015
DOI: 10.1590/s2179-975x3615
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Archaeal and Bacterial communities in a subtropical reservoir

Abstract: Aim: Microbial communities play a central role in environmental process such as organic matter mineralization and the nutrient cycling process in aquatic ecosystems. Despite their ecological importance, variability of the structure of archaeal and bacterial communities in freshwater remains understudied. Methods: In the present study we investigated the richness and density of archaea and bacteria in the water column and sediments of the Itupararanga Reservoir. We also evaluated the relationship between the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…In this study, we investigated the distribution of bacterial communities in the surface and bottom layers of the Billings Reservoir, as well as the environmental conditions that influence their composition. Our results demonstrated that the overall α bacterial diversity represented by the Shannon index was relatively higher in the Billings Reservoir than in other studied freshwater systems: Itupararanga Reservoir, State of São Paulo, Brazil [ 52 ], in Pavin Lake [ 53 ], and Mayinghai, Pipahai, and Gonghai Lakes in China [ 54 ]. Perhaps the greatest value of biodiversity is attributed to intensive anthropogenic disturbance in the reservoir, which may have resulted in increased nutrient discharges, resulting in greater nitrogen and phosphorus concentrations, as indicated in this study.…”
Section: Discussionmentioning
confidence: 82%
“…In this study, we investigated the distribution of bacterial communities in the surface and bottom layers of the Billings Reservoir, as well as the environmental conditions that influence their composition. Our results demonstrated that the overall α bacterial diversity represented by the Shannon index was relatively higher in the Billings Reservoir than in other studied freshwater systems: Itupararanga Reservoir, State of São Paulo, Brazil [ 52 ], in Pavin Lake [ 53 ], and Mayinghai, Pipahai, and Gonghai Lakes in China [ 54 ]. Perhaps the greatest value of biodiversity is attributed to intensive anthropogenic disturbance in the reservoir, which may have resulted in increased nutrient discharges, resulting in greater nitrogen and phosphorus concentrations, as indicated in this study.…”
Section: Discussionmentioning
confidence: 82%